Vivências de mulheres - mães de crianças com Síndrome Congênita do Zika vírus - Graziela Brito Neves Zboralski Hamad (2019)
This research comes from the experiences of women - mothers who contracted the Zika Virus during pregnancy and generated children with Congenital Zika Virus Syndrome, a disease still under investigation because it is an infection known in Brazil only in 2015, caused by an arbovirus of Flavivirus genus, Flaviviridae family, and propagated by a mosquito already endemic in the country, the Aedes aegypti. The high occurrence of cases led the World Health Organization to declare an “emergency situation of international importance” in 2016, as it has repercussions that go far beyond Public Health. Considering the alarming incidence and uncertainty of the prognosis, it is in the face of suspicion and/or confirmation of the disease that the family faces the unexpected and has a concrete need to change their plans and dreams in order to restructure into the new presented situation. Within this context, knowing that the discovery of child malformation is a traumatic experience, we defend the thesis that women - mothers of children with Congenital Zika Virus Syndrome - experience situations of vulnerability and tension, create coping strategies and strengthen themselves in the face of adversity, favoring adaptation. This is a research of a qualitative approach and with interpretative investigation, conducted in a Specialized Center for Rehabilitation, in the city of Campina Grande - PB, from June to November 2017, which aimed to understand the experiences of women - mothers of children with Congenital Zika Virus Syndrome. The research field was conducted by means of an interview with a semi-structured script and genogram and ecomap construction as complementary instruments, as well as notes in a field diary. The Resilience, Stress, Adjustment and Family Adaptation Model proposed by McCubbin and McCubbin was adopted as the theoretical framework of the research. Forty mothers of children with Congenital Zika Virus Syndrome from different cities of the state of Paraíba participated in the research. The thematic-type Content Analysis technique proposed by Bardin was used, which originated five articles: “Congenital Zika Virus Syndrome: knowledge and form of communication of the diagnosis; Interference of daily life in maternal coping with Congenital Zika Virus Syndrome; Demands, vulnerabilities and accumulation of tensions associated with Congenital Zika Virus Syndrome”; Special child, special mother: the sense of the strength of mothers of children with Congenital Zika Virus Syndrome; and strategies of women and their families in coping with Congenital Zika Virus Syndrome”. From strategies used by the women and their families, even in a social context of weaknesses, they were able to reorganize and adapt to the new situation. Understanding these experiences will provide support to the health professionals who deal directly with these women in this context to provide qualified care, being essential in the orientation of care, and possibly favoring the coping and adaptation of the women, of their families, and of the new families who may have children with Congenital Zika Virus Syndrome.